Duration of the menopausal transition is longer in women with young age at onset: the multiethnic Study of Women's Health Across the Nation. Issue 2 (February 2017) - Paramsothy, Pangaja; Harlow, Siobán D.; Nan, Bin; Greendale, Gail A.; Santoro, Nanette; Crawford, Sybil L.; Gold, Ellen B.; Tepper, Ping G.; Randolph, John F.
Abstract: Objective: The menopausal transition (MT) is a critical period associated with physiologic changes that influence women's long-term health and longevity. Information is, however, limited regarding factors that influence age at the onset of the MT and its duration (ie, time from MT onset to the final menstrual period). Methods: We analyzed data for 1, 145 women from four sites of the Study of Women's Health Across the Nation who participated in the menstrual calendar substudy, had the start of the MT identified, and had no missing covariate information. Participants included from four racial/ethnic groups: African American, white, Chinese, and Japanese. Women completed daily menstrual calendars from 1996 to 2006 and questions on hormone therapy use monthly. Baseline measures included education, economic strain, and menstrual cycle characteristics. Annual measures included height, weight, and smoking status. Cox proportional hazards models were used to analyze the data. Results: The adjusted median duration of the MT ranged from 4.37 years among the oldest age-at-onset quartile to 8.57 years among the youngest age-at-onset quartile ( P  < 0.001). Cigarette smoking was associated with an earlier onset ( P  < 0.001) and a shorter duration ( P  < 0.001). African American women had a longer duration ( P  = 0.012) than white women. Body mass index was associated with a later onset of the MT ( P  = 0.001) but not its duration. Conclusions: The duration of the MT was largely influenced by the age at which it began: earlier onset was associated with a longer transition. This finding provides a strong rationale for developing improved markers of the onset of the early MT.